2022
DOI: 10.1038/s41598-022-12361-8
|View full text |Cite
|
Sign up to set email alerts
|

The isolation and expression analysis of cinnamate 4-hydroxylase and chalcone synthase genes of Scrophularia striata under different abiotic elicitors

Abstract: The phenylpropanoid pathway serves as a rich source of metabolites in plants, and it is considered as a starting point for the production of many other important compounds such as the flavonoids, flavonols, coumarins, and lignans. Scrophularia striata is a member of the Lamiaceae family with some biological activities similar to flavonoid compounds such as antioxidant, antibacterial, anti-inflammatory and analgesic activities. Cinnamate 4-hydroxylase (C4H) and Chalcone synthase (CHS) are key enzymes of the phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Numerous studies have shown that the synthesis of polyphenols and flavonoids is regulated by genetics [ 13 , 14 , 15 ]. The flowers and leaves are also known to be the primary sites of storage and photosynthesis for these compounds [ 16 , 17 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have shown that the synthesis of polyphenols and flavonoids is regulated by genetics [ 13 , 14 , 15 ]. The flowers and leaves are also known to be the primary sites of storage and photosynthesis for these compounds [ 16 , 17 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…MYB1 is involved in the activation of the chalcone synthase gene (CHS) and dihydroflavonol reductase gene (DFR) [ 44 ]. CHSs are key enzymes of the phenylpropanoid pathway, and the phenylpropanoid pathway is the starting point for the synthesis of flavonoids and flavonols [ 45 ]. DFR plays a key role in the biosynthesis of anthocyanins and proanthocyanidins (belonging to flavonoids) [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic engineering approaches have been demonstrated as an effective way of increasing the production of flavonoids [ 35 ]. While the application of CRISPR/Cas9 technology for manipulating the metabolite biosynthetic pathways in microorganism cells, such as bacteria and fungi, has become a widely used technique [ 36 , 37 , 38 ], the use of this technology for the same purpose in plants is scarce.…”
Section: Discussionmentioning
confidence: 99%